Automated measurement of repetitive behavior using the Microsoft Kinect: a proof of concept. (18th October 2020) - Maharaj, André V.; Gutierrez, Anibal; Cueto, Carlos; Cadavid, Steven
Abstract: The Microsoft Kinect is a motion‐sensing device that enables users to interact with a computer through body movements. The Kinect was initially developed for video game users (e.g., Microsoft Xbox) although another important use may be as an automated system for measuring human behavior. To demonstrate the potential utility of the Kinect for behavioral measurement, we asked adults to perform various repetitive behaviors while in view of the Kinect sensor. Data collected from Kinect was analyzed via the Matrix Laboratory (MATLAB) program generating frequency of occurrences of repetitive behavior. To assess validity of the automated recording measurement, Kinect data were compared to frequency data obtained via direct human observation. Overall, there was a high‐level of agreement (92%) between measurement procedures (automated vs. human), although the automated system tended to result in slightly lower frequencies (false negatives) than was captured via human observation. Based on these findings, the Kinect technology showed solid potential as a tool for the automatic measurement of behavior. Suggestions for methodical refinement and future evaluation are discussed.